Literatur Review: Pendidikan Bahasa Arab di Era Digital - Ihwan Mahmudi; Didin Ahmad Manca; Amir Reza Kusuma (PT FORMOSA CENDEKIA GLOBAL, 2022)
One alternative to learning Arabic in the digital era is bold digital learning. Today, the process of learning Arabic in Indonesia is growing rapidly. The move from the facet class to the bold class applies facet adjustments in the learning approach. This study uses a literature review method. Data sources are books, articles, and other related sources. The data analysis technique uses data collection, data grouping, data presentation, and inference procedures. Data reliability is verified through source triangulation and technical triangulation. The results show that there are three approaches that are suitable for learning Arabic in this digital era: the contextual approach, the constructivist approach, and the behaviorist approach. Choose an approach that considers the needs and learning conditions of students. Each approach can be implemented using various techniques and techniques. Incorporating these three approaches into Arabic learning provides students with many opportunities for self-taught and language skills development through the various digital media platforms available.